The use of zakat revenue in Islamic financing: jurisprudential debate and practical feasibility - Mahmud , Mek Wok; Shah Haneef, Sayed Sikandar (SIME Journal, 2009)
Recent juristic debate rages around the possibility of using zakah revenue in Islamic law of public finance to better realize its intended poverty eradication goal. At the theoretical level, both the proponents and opponents employ extensive juristic argumentations to support their points of contention. The thrust of the proponents argument is that zakah without productive implementation would not serve its designated goal of poverty alleviation while the opponents countered this case by saying that zakah collection is primarily designed to be immediately disbursed to the consumption needs of the recipients and not vice versa. In practice, however, it seems that the arguments by the proponents is favored as some counties like Kuwait and Malaysia, aside from providing handouts, also finance health care and education for the poor and needy. Accordingly, in our considered opinion, these issues need to be revisited with the primary aim of identifying a balanced legal stand and a feasible institutional framework which takes into full account both the consumption needs and future self-sufficiency of the deserving recipients. To this end, this paper begins by briefly outlining some theoretical aspects of zakah. Then, it proceeds to critically examine the juristic debate surrounding the permissibility of zakah utilization for financing Islamic socio-economic infrastructure. And lastly, it reviews the proposed framework for such utilization with the idea of advancing some jurisprudentially consistent proposals for further academic explorations.